Comparative Study on the Efficiency of Bangladeshi Conventional and Islamic Life Insurance Industry: A Non-Parametric Approach - Rahman, Md. Azizur (Asian Business Review, 2013)
This study endeavor is to examine the efficiency in the both life insurance and life Takaful industry of Bangladesh. The study used Data Envelopment Analysis (DEA) to explore the contributions of technical and efficiency changes to the growth of productivity in the life insurance industries of Bangladesh by using descriptive statistics such as mean, median, standard deviation, minimum & maximum and efficiency concerning the generalized output-oriented Malmquist index for the years 2009-2011. The output-input data consists of a panel of 13 Life Insurance and Takaful Life companies (10 life insurance and 03 Takaful life) in Bangladesh. This study utilizes two inputs and two outputs, namely, commission and management as well as premium and net investment income, respectively. In the DEA technique, efficiency is measured by the Malmquist index. The Malmquist efficiency measures have two components: the efficiency change and technical change index. Efficiency change is again combined by pure efficiency and scale efficiency. It is found that, on geometric mean, the TFP of the Conventional life industry is better than Takaful life mainly due to both efficiency and technical changes where the main source of the efficiency change is scale efficiency rather than pure efficiency. Finding of this study indicates that Conventional and Takaful life industry of Bangladesh, the smaller the size of the companies, the higher the probability for the companies to be more efficient in utilizing their inputs to generate more outputs. This work will beneficial for researchers as well as practitioners to better understand the Bangladeshi life insurance industry.JEL Classification Codes: C14, C67, D57, G22